Adipose-Derived Mesenchymal Stem Cells Attenuate Immune Reactions Against Pig Decellularized Bronchi Engrafted into Rat Tracheal Defects - Makoto Hisanaga; Tomoshi Tsuchiya; Hironosuke Watanabe; Koichiro Shimoyama; Mayumi Iwatake; Yukinori Tanoue; Keizaburo Maruyama; Hiroshi Yukawa; Kazuhide Sato; Yoshimi Kato; Keitaro Matsumoto; Takuro Miyazaki; et al. (Organogenesis, 2023)
ABSTRACTDecellularized scaffolds are promising biomaterials for tissue and organ reconstruction; however, strategies to effectively suppress the host immune responses toward these implants, particularly those without chemical crosslinking, remain warranted. Administration of mesenchymal stem cells is effective against immune-mediated inflammatory disorders. Herein, we investigated the effect of isogeneic abdominal adipose-derived mesenchymal stem/stromal cells (ADMSCs) on xenogeneic biomaterial-induced immunoreactions. Peripheral bronchi from pigs, decellularized using a detergent enzymatic method, were engrafted onto tracheal defects of Brown Norway (BN) rats. BN rats were implanted with native pig bronchi (Xenograft group), decellularized pig bronchi (Decellularized Xenograft), or Decellularized Xenograft and ADMSCs (Decellularized Xenograft+ADMSC group). In the latter group, ADMSCs were injected intravenously immediately post implantation. Harvested graft implants were assessed histologically and immunohistochemically. We found that acute rejections were milder in the Decellularized Xenograft and Decellularized Xenograft+ADMSC groups than in the Xenograft group. Mild inflammatory cell infiltration and reduced collagen deposition were observed in the Decellularized Xenograft+ADMSC group. Additionally, ADMSC administration decreased CD8+ lymphocyte counts but increased CD163+ cell counts. In the Decellularized Xenograft+ADMSC group, serum levels of vascular endothelial growth factor and IL-10 were elevated and tissue deposition of IgM and IgG was low. The significant immunosuppressive effects of ADMSCs illustrate their potential use as immunosuppressive agents for xenogeneic biomaterial-based implants.